Impact on post partum amenorrhoea beyond breastfeeding - Shukla, A. K.; Tiwari, A. K.; Yadava, R. C. (International Journal of Health, 2017)
Citing various studies Bongaarts (1980) has concluded that breastfeeding is the principal determinant of post partum amenorrhoea (PPA) and unrestricted breastfeeding is associated with lower fertility. On the other hand many researchers have shown opposite views by saying that other factors are also responsible in affecting the duration of PPA. In this paper, we have investigated the relationship between the two duration variables viz. PPA and breastfeeding utilizing data of NFHS-2. For this purpose, we have controlled the duration of breastfeeding and then investigated whether distribution of PPA duration shows similar pattern in different situations or it varies with the situations. This can help in deciding whether PPA duration is mainly affected by breastfeeding or some other factors are also operating in shaping its distribution. In this context, we show that even after controlling the duration of breastfeeding (keeping breastfeeding at least six months) the percentage of females having PPA duration less than four months, shows large variation according to caste, educational level, standard of living index (SLI) and body mass index (BMI) of females. If breastfeeding would have been the only principal determinant of duration of PPA, this percentage should have remained almost constant! This shows that some other factors beyond breastfeeding are responsible for shaping the distribution of PPA duration of a female.